DIGITAL TRANSFORMATION OF HEALTHCARE IN UZBEKISTAN: THE ROLE OF THE DMED INFORMATION SYSTEM (Eureka Journal of Business, Economics & Innovation Studies, 2026)
This article examines the role of the DMED information system in the digital transformation of the healthcare sector of the Republic of Uzbekistan. The study analyzes the functional structure of DMED, its key modules, and its significance in creating a unified digital healthcare environment. Particular attention is paid to the electronic medical record (MED-ID), electronic prescription system, analytical and monitoring tools, and the integration of telemedicine and mobile applications. The research highlights the impact of DMED on improving the quality and continuity of medical care, enhancing management efficiency, and enabling data-driven decision-making in healthcare administration. The article also identifies key challenges related to digital literacy, data protection, and infrastructure sustainability, emphasizing the importance of further system development in shaping a patient-centered and sustainable healthcare model.
Keywords: Digital healthcare, DMED, electronic medical record, MED-ID, electronic prescription, information system, healthcare management, digital transformation.